Pedagogical adaptation of teaching assistant students to the characteristics of the secondary school curriculum in Kediri City - Nurul Dwi Lestari; Yuni Pratiwi; Titik Harsiati (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
The implementation of the Independent Curriculum requires prospective teachers to be able to adapt pedagogically so that learning designs align with the characteristics of the educational unit. However, research on the pedagogical adaptation of teaching assistant students has focused primarily on teaching practice experiences and has not examined the alignment between Learning Outcomes (CP), Learning Objectives (TP), Learning Objective Paths (ATP), and school characteristics. This study aims to analyze the alignment of the learning designs of teaching assistant students in the Indonesian Language Education Study Program at UIN Syekh Wasil Kediri with the characteristics of high school and vocational high school educational units. The novelty of this research lies in the definition of pedagogical adaptation as a process of aligning learning tools with the school context. The study used a descriptive qualitative method with a phenomenological approach. Data were obtained through document analysis of learning tools, in-depth interviews, and observations of teaching assistant students, mentor teachers, and supervising lecturers. Data were analyzed through data reduction, data presentation, and conclusion drawing.The research results indicate that the CP, TP, and ATP developed by students are appropriate to the characteristics of the educational unit, while the learning models and methods support student needs and school conditions. However, pedagogical adaptation still requires strengthening in terms of contextualization, particularly the integration of vocational characteristics in vocational schools and local contexts in senior high schools. These findings confirm that prospective teachers' pedagogical adaptation is the ability to align curriculum demands with school realities in implementing the Independent Curriculum.